Triple Oxygen Isotope Measurements by Multi-Collector Secondary Ion Mass Spectrometry - Bouden, Nordine; Villeneuve, Johan; Marrocchi, Yves; Deloule, Etienne; Füri, Evelyn; Gurenko, Andrey; Piani, Laurette; Thomassot, Emilie; Peres, Paula; Fernandes, Firmino (Frontiers in Earth Science, 2021)
Secondary ion mass spectrometry (SIMS) is a powerful technique for in situ triple oxygen isotope measurements that has been used for more than 30 years. Since pioneering works performed on small-radius ion probes in the mid-80s, tremendous progress has been made in terms of analytical precision, spatial resolution and analysis duration. In this respect, the emergence in the mid-90s of the large-radius ion probe equipped with a multi-collector system (MC-SIMS) was a game changer. Further developments achieved since then (e.g. stability of the electronics, enhanced transmission of secondary ions, automatic centring of the secondary ion beam, Nuclear Magnetic Resonance (NMR) control of the magnetic field, 1012Ω resistor for the faraday cup (FC) amplifiers allow nowadays to routinely measure oxygen isotopic ratios (18O/16O and 17O/16O) in various matrices with a precision (internal error + reproducibility) better than 0.5‰ (2σ standard error), a spatial resolution smaller than 10 µm and in a few minutes per analysis. This paper focuses on the application of MC-SIMS technique to the in situ monitoring of mass-independent triple oxygen isotope variations.